Reviews of physiology, biochemistry and pharmacology. 173 - Nilius, B.; Tombe, Pieter de; Gudermann, Thomas; Jahn, Reinhard, 1950-; Lill, Roland; Petersen, O. H. (Springer, 2017)
M.T. Rahman, N. Haque, N.H.A. Kassim: Origin, Function and Fate of Metallothionein in Human Blood L. Ribeiro, P. Bastos, T. Gomes: .Catechol-O-methyltransferase (COMT): An Update on its Role in Cancer, Neurological and Cardiovascular Disease. B.M. Fonseca, N. Teixeira, G. Correia-da-Silva: Cannabinoids as Modulators of Cell Death: Clinical Applications and Future Directions.
Keywords: Human physiology.; Molecular biology.; Metabolism -- Disorders.; elektronické knihy; electronic books